Jumping the color line : vernacular jazz dance in American film, 1929-1945 - Trenka, Susie (New Barnet, Hertfordshire : John Libbey Publishing Ltd, 2021)
With a majority of examples taken from marginal film forms, such as shorts and B movies, the book highlights their role in disseminating alternative images of racial and gender identities as embodied by dancers - images that were at least partly at odds with those typically found in major Hollywood productions.
Jazz dance on the silver screen: race, gender, genre -- Doomed divas: Black dancing women in early sound film -- Kids and class acts: male dancers in Black-cast music shorts -- Potential pioneer: the film career of Black tap dancer Jeni LeGon -- Jumpin' at the jukebox, dancin' in the street: dance, race, and space in 1940s soundies -- Harlem to Hollywood: Whitey's Lindy Hoppers and the crossover success of a Black dance -- "A savage exhibition"? Swing and White youth culture in B movies -- Dance history, the swing dance revival, and vintage movies in the digital age.
Print version record.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 01, 2021).
eBooks on EBSCOhost
Keywords: Jazz dance -- History; African American dancers -- History; Racism and the arts -- United States -- History; Dance in motion pictures, television, etc. -- History; Jazz (Danse) -- Histoire; Danseurs noirs américains -- Histoire; Racisme et arts -- États-Unis -- Histoire; African American dancers; Dance in motion pictures, television, etc; Jazz dance; Racism and the arts; United States; History & Criticism; Dance; PERFORMING ARTS; Jazz; Film & Video; History; Electronic books